2015
DOI: 10.1503/cjs.014814
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-assisted percutaneous endoscopic gastrostomy: insertion of a skin-level device using a tear-away sheath

Abstract: Background: This study describes our experience with the placement of a skin-level gastrostomy device (MIC-KEY) in a single procedure. Methods:We identified infants, children and young adults who underwent laparoscopicassisted percutaneous endoscopic gastrostomy (LAPEG) tube insertion between October 2009 and June 2013. The steps of this procedure include upper endoscopy, single-port laparoscopy, gastropexy via percutaneous T-fasteners and placement of a skin-level gastrostomy device (MIC-KEY) using a "push" t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 24 publications
2
20
0
4
Order By: Relevance
“…In the large Swedish series of 201 patients getting PEG-T, median time for PEG-T placement was 20 minutes 6 . We did not see a decrease in operating time or in the frequency of patients experiencing early complications in our study as reported in other series 7 8 , but this may partly be explained by the relatively high number of physicians involved. Jacob et al found the PEG-T procedure to be technically challenging, and they experienced a significant learning curve with regard to both complications and operating time 7 .…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…In the large Swedish series of 201 patients getting PEG-T, median time for PEG-T placement was 20 minutes 6 . We did not see a decrease in operating time or in the frequency of patients experiencing early complications in our study as reported in other series 7 8 , but this may partly be explained by the relatively high number of physicians involved. Jacob et al found the PEG-T procedure to be technically challenging, and they experienced a significant learning curve with regard to both complications and operating time 7 .…”
Section: Discussionsupporting
confidence: 47%
“…Compared to other reported series of PEG-P, this is a high number 13 14 . In 2 series of PEG-T 6 7 , there was no report of any early dislodgment, while Livingston et al reported this in 2 of 92 patients 8 . We have no apparent explanation for the high frequency of early dislodgment.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations